STUDY OF FISHING PORT FACILITIES REQUIREMENT’S IN TERKUL VILLAGE DISTRICT OF RUPAT BENGKALIS REGENCY PROVINCE RIAU - Purba, Ervi Natalia; Zain, Jonny; ', Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
AbstrackThis research was conducted on 10 – 17 october 2015 with the aim to determine the type and size / capacity of the port facility in accordance with the needs of fishermen and other actors in order to expedite and facilitate the activities of fishing and landing and marketing of the fish and other activities with using the survey method. The size of the required facilities include 93 meter long loading docks, unloading quay length of 17.96 meters, 35791.1 meters wide port pool, pool depth is 1.93 meters, auction room area is 8.06 meter², and needs freshwater supplies as much as 12376.29 liters, liters of fuel needs as much 10007.14 and ice plant with a capacity of 10576.36 kg. From the results of these calculations also showed that the type of fishing ports to be built is of type D or small-scale fish landing base or also called the Fish Landing Place.Keywords: Port Facility Type, Size Fishing Port Facilities